Cultural and Biological Control Measures Against Corm Rot Disease of Tannia (Xanthosoma sagittifolium (L.) Schott): Impact on Growth and Yield - Thavabalachandran, Mangaleswary; R.G.A.S., Rajapakse (JOURNAL OF ROOT CROPS, 2015)
Tannia (Xanthosoma sagittifolium (L.) Schott), a backyard tuber crop and a low subsistence staple food, is now an important commercial crop in Sri Lanka. It is a shade loving crop relatively free from pest problems. However, corm rot (leaf yellowing) disease caused by Rhizoctonia spp. is one of the major constraints in the profitable cultivation of the crop. At present this disease has reached an epidemic level in most of the tannia cultivated areas. The main symptoms of the disease are yellowing of leaves, stunted plant growth and rotting of tubers. Experiments were conducted at Horticultural Crops Research and Development Institute (HORDI), Gannoruwa for three consecutive seasons (2006-2009) for the management of soil borne disease, corm rot (leaf yellowing) in tannia. Four cultural practices (planting on ridges, pits, flat land and intercropping with maize) and three soil treatments with Trichoderma (at the time of planting, one and two months after planting) were evaluated. The disease incidence was very low in soils treated with Trichoderma based biocontrol agent. The results revealed that soil treatment with Trichoderma gave significantly higher yields (13.5 t ha-1) and mean number of cormels per plant and mean cormel weight. Therefore, Trichoderma based biocontrol agent was found to be effective for the management of soil borne diseases like corm rot and getting higher productivity.